Characterizing a mosquito gut bacterial community - Kemp, Janet A., author; Lang, Gail M., author; DuTeau, Nancy M., author (Colorado State University. Libraries, 2005)
Mosquitoes are common vectors of devastating diseases that infect both humans and animals. Methods of control, such as insecticides and vaccines, are losing their effectiveness. Alternative strategies need to be considered. Paratransgenesis is one method of blocking transmission of disease from mosquito to host. Paratransgenesis is the genetic engineering of symbiotic or commensal bacteria to produce products that block pathogen transmission. This research project looked at characterizing the bacterial community of adult female Aedes aegypti to find candidates for paratransgenesis. We identified 72 diverse culturable bacterial isolates present in the midgut and on the exoskeleton of this mosquito. We examined the difference between the midgut bacterial community of blood-fed and sugar-fed female adults. We also found that approximately 10% of the total bacterial species found in the midgut are culturable, which is consistent with studies from other natural bacteria consortia.
Keywords: Aedes aegypti -- Physiology; Aedes aegypti -- Molecular aspects; Mosquitoes as carriers of disease